2020
DOI: 10.3390/md18120610
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperuricemic Effects of Astaxanthin by Regulating Xanthine Oxidase, Adenosine Deaminase and Urate Transporters in Rats

Abstract: This study was designed to investigate the effects and underlying mechanisms of Astaxanthin (AST) on high-fructose-induced hyperuricemia (HUA) from the perspectives of the uric acid (UA) synthesis and excretion in rat models. Following six weeks of a 10% fructose diet, the level of serum UA effectively decreased in the AST groups as compared to the model group. The enzymatic activities of xanthine oxidase (XOD) and adenosine deaminase (ADA) were significantly inhibited, and the mRNA expression levels of XOD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…However, if blood levels of UA are high, UA is crystallized and deposited as monosodium urate (MSU) in the joints and tissues and is closely correlated with the occurrence of gout and inflammation. MSU can trigger the production of the pro-inflammatory mediators nuclear factor-kappa B (NF-κB) and tumor necrosis factor-alpha (TNF-α) via Toll-like receptor 4 (TLR4) . In addition, both ROS and MSU are well-known activators of the nucleotide-binding oligomerization domain-like receptor family containing pyrin domain 3 (NLRP3) inflammasome .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if blood levels of UA are high, UA is crystallized and deposited as monosodium urate (MSU) in the joints and tissues and is closely correlated with the occurrence of gout and inflammation. MSU can trigger the production of the pro-inflammatory mediators nuclear factor-kappa B (NF-κB) and tumor necrosis factor-alpha (TNF-α) via Toll-like receptor 4 (TLR4) . In addition, both ROS and MSU are well-known activators of the nucleotide-binding oligomerization domain-like receptor family containing pyrin domain 3 (NLRP3) inflammasome .…”
Section: Introductionmentioning
confidence: 99%
“…MSU can trigger the production of the pro-inflammatory mediators nuclear factor-kappa B (NF-κB) and tumor necrosis factor-alpha (TNF-α) via Toll-like receptor 4 (TLR4). 11 In addition, both ROS and MSU are well-known activators of the nucleotide-binding oligomerization domain-like receptor family containing pyrin domain 3 (NLRP3) inflammasome. 12 The NLRP3 inflammasome serves as a platform for the activation of interleukin (IL)-18 and IL-1β secretion through the stimulation of apoptosis-associated speck-like protein containing a C-terminal caspase recruitment domain (ASC) and cysteinyl aspartate specific proteinase 1 (caspase-1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, the uric acid excretion transporters ABCG2 and OAT1 are responsible for regulating uric acid excretion via secreting uric acid into the urethra [ 43 ]. Previous studies showed that six weeks of treatment of a 10% fructose diet altered the urate transporter regulation and increased the uric acid serum level [ 44 ]. Moreover, many natural extracts have been explored for efficacy using animal models of hyperuricemia such as quercetin [ 36 ], resveratrol [ 45 ], fucoxanthin [ 46 ], green tea polyphenols [ 47 ], and longan extract [ 48 ], which can inhibit the reabsorption of uric acid by regulating uric acid-related transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the levels of renal transporters should attract clinician attentions. In animal models, the OAT1/3, OCT2, and BCRP expressions are decreased under the pathological condition, whereas MDR1 and MRP2/4 expressions are not affected by hyperuricemia (Nishizawa et al, 2019;Le et al, 2020). A growing number of studies have reported that OAT1/3, OCT2, and BCRP are involved in urate efflux from epithelial cells to urine (Taniguchi et al, 2021), and these transporters have been extensively studied in the hyperuricemia.…”
Section: Effect Of Metabolic Disease On Drug Transporters In Kidneymentioning
confidence: 99%